Falha a fala, fala a bala: a construção épica em cidade de Deus, de Paulo Lins - Pereira, Edineyalison Wallas Henriques Ferreira (2013)
In this piece of work, entitled Falha a fala, fala a bala: The epic construction in Cidade de Deus, by Paulo Lins, we propose a textual analysis of this novel, in which we seek to comprehend how the narrative techniques used and the hero characterization proposed by the narrator are articulated. There is no unity in Cidade de Deus narrative voice, in the sense of a person recognizable in the real world, but it is formed by a mix of different points of view, what causes moral judgments impossible to find a unity. The dynamic form of the narrator shares with the character the incapacity to observe their reality as a whole, and both are involved in an ideology that alienates them and represses their voices as autonomous human beings. Thus, the techniques used by Paulo Lins work as irony, for it conveys that, if the use of such techniques may make the novel a commercial product, on the other hand, the same procedures are revealed to be inefficient to produce positive solutions to the drama theme of the text. In our approach, we follow the footsteps of preexistent critics that seeks to identify marks of literality in Lins novel, and recognize that the techniques used by the narrator, such as the detailed description of violence and the fast pace of action scenes, are not just a thoughtless reproduction of clichés, but has a recognizable function in a text the seeks to be as realistic as possible.